Early Warning Of Leaking Lpg Gas Through Short Message Service (Sms) And Loudspeaker Tool Using Arduino Uno - Novi Rahayu (Journal of Applied Engineering and Technological Science (JAETS), 2020)
At this time, the function of Liquified Petroleum Gas (LPG) is very important for human life, both in the household and industry. However, this can have a negative impact, especially in terms of if there is no known leaky hole that can cause an explosion and fire. The main factors that can cause the leaking of gas cylinders include improper installation of regulators, poor quality of tube sealing rings, quality of gas cylinders, non-regulators of the Indonesian National Standard (SNI), tear gas hose due to animals such as mice . The way of working from these tools when the MQ-6 sensor detects LPG gas above 100 ppm, the sensor will send data to the microcontroller on Arduino Uno for giving a response as a buzzer as an alarm, the loudspeaker as gives notification the sound of danger and send information in the form of SMS to the home owner. The test results that this warning system can indicate if any leaking on the gas concentration of 117 to 457 ppm and the duration of sending SMS between 3 to 182 seconds from five tests given in three different places.